2018
DOI: 10.1186/s12967-018-1616-2
|View full text |Cite
|
Sign up to set email alerts
|

The changes of immunoglobulin G N-glycosylation in blood lipids and dyslipidaemia

Abstract: BackgroundAlternative N-glycosylation has significant structural and functional consequences on immunoglobulin G (IgG) and can affect immune responses, acting as a switch between pro- and anti-inflammatory IgG functionality. Studies have demonstrated that IgG N-glycosylation is associated with ageing, body mass index, type 2 diabetes and hypertension.MethodsHerein, we have demonstrated patterns of IgG glycosylation that are associated with blood lipids in a cross-sectional study including 598 Han Chinese aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 57 publications
7
55
0
Order By: Relevance
“…Our previous studies have shown that the decreasing galactosylation and sialylation and the increasing bisecting GlcNAc are risk factors of many inflammatory and chronic diseases (Adua et al, 2017), including hypertension (Wang et al, 2016b), stroke (Liu et al, 2018b), T2DM (Lemmers et al, 2017), and dyslipidemia (Liu et al, 2018a), which are consistent with this study. The changes to IgG N-glycans, which were reported in metabolic syndrome, hypertriglyceridemic waist phenotype, and abdominal obesity in this study, might suggest that aberrant glycosylation of IgG is not disease specific, but a general phenomenon associated with reducing the anti-inflammatory function of circulating IgG.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our previous studies have shown that the decreasing galactosylation and sialylation and the increasing bisecting GlcNAc are risk factors of many inflammatory and chronic diseases (Adua et al, 2017), including hypertension (Wang et al, 2016b), stroke (Liu et al, 2018b), T2DM (Lemmers et al, 2017), and dyslipidemia (Liu et al, 2018a), which are consistent with this study. The changes to IgG N-glycans, which were reported in metabolic syndrome, hypertriglyceridemic waist phenotype, and abdominal obesity in this study, might suggest that aberrant glycosylation of IgG is not disease specific, but a general phenomenon associated with reducing the anti-inflammatory function of circulating IgG.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate that high levels of agalactosylated N-glycans and bisecting GlcNAc may be associated with higher measures of hypertriglyceridemic waist phenotype, which may increase the risk of coronary artery disease. These findings are strongly supported by previous evidence that GP5 and GP11 are positively associated with dyslipidemia (Liu et al, 2018a). Therefore, GP5, GP10, GP 11, and GP15…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also, reduced LDLR glycosylation was found to result in reduced lipid binding and endocytosis 41 . Recently, changes in IgG glycosylation have been associated with blood lipids and dyslipidemia in Han Chinese 42 . A similar role for glycosylation was also reported in relation to coagulation proteins, where mutations affecting glycosylation were associated with different enzymatic activity 37 .…”
Section: Discussionmentioning
confidence: 99%